Mannose‐Decorated Multicomponent Supramolecular Polymers Trigger Effective Uptake into Antigen‐Presenting Cells. (17th April 2018) - Straßburger, David; Stergiou, Natascha; Urschbach, Moritz; Yurugi, Hajime; Spitzer, Daniel; Schollmeyer, Dieter; Schmitt, Edgar; Besenius, Pol
Abstract: A modular route to prepare functional self‐assembling dendritic peptide amphiphiles decorated with mannosides, to effectively target antigen‐presenting cells, such as macrophages, is reported. The monomeric building blocks were equipped with tetra(ethylene glycol)s (TEGs) or labeled with a Cy3 fluorescent probe. Experiments on the uptake of the multifunctional supramolecular particles into murine macrophages (Mφs) were monitored by confocal microscopy and fluorescence‐activated cell sorting. Mannose‐decorated supramolecular polymers trigger a significantly higher cellular uptake and distribution, relative to TEG carrying bare polymers. No cytotoxicity or negative impact on cytokine production of the treated Mφs was observed, which emphasized their biocompatibility. The modular nature of the multicomponent supramolecular polymer coassembly protocol is a promising platform to develop fully synthetic multifunctional vaccines, for example, in cancer immunotherapy. Abstract : Self‐assembled macrophage targets : A modular route is presented to prepare multifunctional supramolecular polymers based on self‐assembled dendritic peptide amphiphiles decorated with mannosides to effectively target antigen‐presenting cells, such as macrophages. The multicomponent co‐assembly protocol is a powerful platform for the development of fully synthetic multifunctional vaccines.